IMPLEMENTASI PROGRAM JAMINAN PEMELIHARAAN KESEHATAN GRATIS DI PUSKESMAS GROGOL KABUPATEN SUKOHARJO - Wahyu Adi Prasetyo, Bagus Suryono (GEMA, 2015)
This research aims to know implementation of free of charge health care in Puskesmas of grogol based on the rule num. 36 Year of 2009 regarding to Health andÂ theÂ rightsÂ ofÂ patientÂ againstÂ servicesÂ inÂ PuskesmasÂ ofÂ GrogolÂ accordingÂ to program of free of charge health care insurance. BasedÂ onÂ theÂ resultÂ ofÂ theÂ researchÂ performedÂ canÂ beÂ concludedÂ that whollyÂ muchÂ ofÂ freeÂ ofÂ chargeÂ healthÂ careÂ insuranceÂ patientsÂ areÂ satisfiedÂ with implementationÂ andÂ theÂ rightsÂ ofÂ patients Â againstÂ freeÂ ofÂ chargeÂ healthÂ care services which have been performed by Puskesmas of Grogol. Although there are several patients felt that their rights have not yet fulfilled. It happened because the patient of Jamkesmas (community health insurance) itself didnât understand their rightsÂ asÂ patientÂ ofÂ freeÂ chargeÂ healthÂ careÂ insuranceÂ inÂ PuskesmasÂ Grogol. But PuskesmasÂ ofÂ GrogolÂ hasÂ whollyÂ implementedÂ fulfillmentÂ ofÂ goodÂ servicesÂ the rightsÂ ofÂ patientÂ becauseÂ itÂ hasÂ beenÂ inÂ accordanceÂ withÂ governmentÂ rule.